Analisis Pelaporan Keuangan Segmen Pada PT. Bayan Resources Tbk - Putri Dasti S Harahap; Atika Fitriani; Sarifah Aini Hasibuan; Melki Wijaya; Siti Rodiah (Universitas Teuku Umar, 2023)
Companies that go public on average will definitely have financial reports, because to find out whether the company provides financial statement data tools that describe the company's performance in each period as a tool for making decisions and being accountable to related parties. This report is made with the aim of making it easier for report users to see the total behind the consolidated figures to the individual components that make up the entity. One of the financial statements is a segment financial report. The segment financial report is a report that provides information data that is important enough to determine the company's performance in the form of profit contributions that grow in various geographic industrial areas. This research was taken from a sample of PT.Bayan Resources Tbk from the period 2018-2022 in accordance with PSAK number 5. PT.Bayan Resources Tbk has 2 segments, namely coal and non-coal segments. Data was collected through literal research techniques. Data analysis is done quantitatively. The technique used is the Purposive Technique which is tested there is a revenue test, asset test and profit and loss test. The results of this study indicate that the segments at PT Bayan Resources Tbk in the profit and loss and asset tests have not met the 10% test in segment reporting.